Analysis of Marketing Strategy of Entrepreneurship of MSME Bakso Dono Bandar Lampung - Daud, Syahril; Ferdian, Yolanda; Chestagavrila , Orvala; Aldino, M Farhan (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
Study This aiming For analyze marketing strategies entrepreneurship applied by UMKM Bakso Dono in Bandar Lampung. The research method used is studies descriptive qualitative with technique data collection through observation, interviews, and documentation. Research results show that UMKM Bakso Dono uses various marketing strategies, including digital marketing through social media, increasing quality products, as well as service good customer For attract and retain customers. The obstacles faced is tight market competition and limited business capital. Efforts made For overcome constraint the covering innovation more products and promotions effective. This strategy expected can helping Bakso Dono UMKM to grow in a way sustainable and improving Power compete in the local market.